Content Validity and Authenticity of the 2012 English Test in the Senior High School National Examination - Widyaningrum, Frisca Ayu Desi; Prabandari, Carla Sih (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2013)
This paper discusses content validity and authenticity of the English test items in National Examination (UN) year 2012. It is worth discussion because UN, which was administered nationally, was the most important standardized test to assess Indonesian students’ competence. The study aimed to find out how valid the content of the English test items of National Examination year 2012 for senior high schools isand how authentic the English test items of National Examination year 2012 for senior high schools is. The writers employed a qualitative research with document analysis to conduct the analysis of both content validity and authenticity of the English test items. The data were obtained from the document and analyzed by using checklists. Besides, to maintain the validitiy of the analysis, a triagulation was done by distributing aquestionnaire to four experts in language assessment. There were twofindings resulted form the analysis. First, the content of the National Examination year 2012 was 98.8% valid since almost all of the contents were relevant to the test specifications. However, there were three reading test versions which failed to represent kinds of texts, namely explanation text. Second, the National Examination year 2012 met the criteria of authenticity with percentage 79.5% since some listening and reading test items failed to conform to authenticity criteria. Natural language use, the relevance of the test topics, and real-world representativeness became problematic aspects to meet the higher standard of authenticity. DOI: https://doi.org/10.24071/llt.2013.160103